Computer Aided–Designed, 3-Dimensionally Printed Porous Tissue Bioscaffolds for Craniofacial Soft Tissue Reconstruction. (January 2015) - Zopf, David A.; Mitsak, Anna G.; Flanagan, Colleen L.; Wheeler, Matthew; Green, Glenn E.; Hollister, Scott J.
Objective: To determine the potential of an integrated, image-based computer-aided design (CAD) and 3-dimensional (3D) printing approach to engineer scaffolds for head and neck cartilaginous reconstruction for auricular and nasal reconstruction. Study Design: Proof of concept revealing novel methods for bioscaffold production with in vitro and in vivo animal data. Setting: Multidisciplinary effort encompassing 2 academic institutions. Subjects and Methods: Digital Imaging and Communications in Medicine (DICOM) computed tomography scans were segmented and utilized in image-based CAD to create porous, anatomic structures. Bioresorbable polycaprolactone scaffolds with spherical and random porous architecture were produced using a laser-based 3D printing process. Subcutaneous in vivo implantation of auricular and nasal scaffolds was performed in a porcine model. Auricular scaffolds were seeded with chondrogenic growth factors in a hyaluronic acid/collagen hydrogel and cultured in vitro over 2 months' duration. Results: Auricular and nasal constructs with several types of microporous architecture were rapidly manufactured with high fidelity to human patient anatomy. Subcutaneous in vivo implantation of auricular and nasal scaffolds resulted in an excellent appearance and complete soft tissue ingrowth. Histological analysis of in vitro scaffolds demonstrated native-appearing cartilaginous growth that respected the boundaries of the scaffold. Conclusion: Integrated, image-based CAD and 3D printing processes generated patient-specific nasal and auricular scaffolds that supported cartilage regeneration.